Social Media Marketing, Brand Image, e-WOM, and Service Quality as Drivers of Trust in International Personal Shopper Services - Erilia Kesumahati; Glenis Doren Lim; Wisnu Yuwono (Journal of Enterprise and Development (JED), 2025)
Purpose: This study examines the influence of social media marketing, electronic word of mouth (e-WOM), service quality, and brand image on trust in international personal shopper services, commonly referred to in Indonesia as jastip (jasa titip).Method: This research employs a quantitative approach utilizing Partial Least Squares Structural Equation Modelling (PLS-SEM). The study collects data from 250 users of Jastip services through social media platforms such as Instagram, Shopee, and TikTok.Result: The findings reveal that all independent variables—social media marketing, e-WOM, service quality, and brand image—significantly affect consumer trust. Among these variables, e-WOM and brand image demonstrate the strongest influence. Additionally, social media marketing positively impacts brand image, service quality, and e-WOM.Practical Implications for Economic Growth and Development: This study highlights the crucial role of digital platforms in fostering trust and consumer engagement in international shopping services. By strengthening social media strategies, Jastip providers can enhance customer loyalty, thereby indirectly supporting cross-border commerce and contributing to the growth of the digital economy.Originality/Value: This study integrates four key variables into a comprehensive model to elucidate trust in personal shopper services. While previous studies often examine these variables in isolation, this research provides a holistic perspective on how digital marketing efforts and consumer perceptions collectively shape trust in consumer-to-consumer (C2C) business models.